Thanksgiving cats - Marzollo, Jean.; Wilhelm, Hans, 1945- (New York : Scholastic, 1999)
Cats celebrate Thanksgiving by growing lots of vegetables, raising turkeys, making pies, preparing a feast, giving thanks, and enjoying the food.
"Cartwheel books."
380
Keywords: Thanksgiving Day -- Fiction; Cats -- Fiction; Stories in rhyme